Effect of facial emotion recognition learning transfers across emotions - Bi, Taiyong; Luo, Wei; Wu, Jia; Shao, Boyao; Tan, Qingli; Kou, Hui (Frontiers in Psychology, 2024)
Perceptual learning of facial expression is shown specific to the train expression, indicating separate encoding of the emotional contents in different expressions.However, little is known about the specificity of emotional recognition training with the visual search paradigm and the sensitivity of learning to near-threshold stimuli. In the present study, we adopted a visual search paradigm to measure the recognition of facial expressions. In Exp1, Exp2, and Exp3, subjects were trained for eight days to search for a target expression in an array of faces presented for 950ms, 350ms, and 50ms respectively. In Exp4, we trained subjects to search for a target of a triangle, and tested them with the task of facial expression search. Before and after the training, subjects were tested on the trained and untrained facial expressions which were presented for 950ms, 650ms, 350ms, or 50ms. Results showed that training led to large improvements in the recognition of facial emotions only if the faces were presented long enough (Exp1: 85.89%; Exp2: 46.05%). Furthermore, the training effect could transfer to the untrained expression. However, when the faces were presented briefly (Exp3), the training effect was small (6.38%). In Exp4, the results indicated that the training effect could not transfer across categories. In conclusion, our findings revealed cross-emotion transfer for facial expression recognition training in a visual search task. In addition, learning hardly affects the recognition of near-threshold expressions.